Cepstral Analysis of Voice in Persons With Vocal Nodules - Radish Kumar, B.; Bhat, Jayashree S.; Prasad, Neitica (Journal of voice, 2010)
Traditional measures of dysphonia were reported to be unreliable, and the measurements of cepstral peak prominence (CPP) have been shown to correlate well with perceptions of breathiness. Hence, the present study was hypothesized that there would be abnormal reduction of the cepstral peak in the speakers with vocal nodules relative to the normal controls as they are characterized by hoarse and breathy voice due to inadequate closure of vocal folds. Phonation of sustained vowel /a/ was subjected to acoustic analysis using Computerized Speech Lab (CSL model 4150) software. The vowels were analyzed acoustically with the measurement of CPP. Independent t test was employed to compare the significant differences between the clinical and the control groups in both males and females. The results revealed significant differences across the two groups at P < 0.05. The obtained results were discussed with respect to the underlying pathophysiology. The present study investigated the CPP in subjects with vocal nodules. Cepstral deviations in the clinical group are explained due to the presence of laryngeal pathology leading to the lower values of CPP.